(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: Idioms play a crucial role in every language. They enhance communication with vivid and engaging ideas, adding richness, color, and depth. However, where do these phrases originate from? What is the reason behind expressions such as "raining cats and dogs" or "burning the midnight oil"? Numerous idioms have intriguing historical, cultural, or even literal backgrounds. This article will delve into the origins of famous English idioms, revealing how they transformed into the phrases we commonly use.